اردو ڈراما کی روایت میں رامائن کا کردار - Chand Lal; Dr. Shazia Ambareen (Khayaban - خیابان, 2022)
Ramayana is the story of Rama. Ramayana is classical text of Sanskrit language. This great epic was composed by Sanskrit poet VALMIKI in 500 B.C .It is great source of Indian mythology. It has a great importance in indology .It laid great impact on Urdu literature, due to its importance more than 100 urdu translation of this epic has been done. It played a important role in Urdu drama tradition.